Computer simulation of the surface structures of WO3 - Oliver, P; Parker, S; Egdell, R; Jones, F (1996)
Surface energies have been calculated for the {110}, {111} and five reconstructions of the {001} surface of idealised cubic tungsten oxide (WO3). This gave surface energies of 1.58 J m-2 for the perfect {110} surface, 4.89 J m-2 for the most stable oxygen terminated {111} surface and 1.39 J m-2 for the most stable (√2 × √2)R45° reconstruction of the {001} surface. The latter has been observed experimentally using scanning tunnelling microscopy on the monoclinic phase of WO3. More complex reconstructions were considered for the {110} and {111} surfaces. On microfacetting, the {110} surface was slightly destabilised, but only by 0.06 J m-2 to 1.64 J m-2, suggesting that there could be regions on the surface that become facetted on annealing. In contrast, the {111} surface was stabilised to a large extent from 4.89 J m-2 to 1.50 J m-2 for the oxygen terminated surface. Thus it is predicted that cleaving and annealing the {111} surface will result in a facetted surface. In addition to considering the stoichiometric surfaces we modelled the reduced {001} surface by the introduction of oxygen vacancies and WV. This led to negative surface energies at high coverages indicating that, thermodynamically, the surface will form spontaneously.